American Legacy: Our National Forests - Brower, Kenneth; Prepared by the Book Division, National Geographic Society (Washington, D.C. The Division, 1997)
This book describes the rugged and natural beauty of our National Forests with many colorful and breathtaking photos and maps.
Includes illustrations and Index.
Keywords: National parks and reserves